Current Approaches to Osteoid Osteoma and Minimally Invasive Surgery-A Minireview and a Case Report - Cerny, Jan; Soukup, Jan; Cerna, Sarka; Novotný, Tomáš (Journal of clinical medicine, 2022)
Osteoid osteoma is a benign bone tumor typically affecting the long bones of the lower limbs in young male patients. The lesion can be asymptomatic but, in most cases, patients present with characteristic nocturnal pain that is very responsive to the administration of non-steroidal anti-inflammatory drugs. Although osteoid osteomas can regress spontaneously over time, surgical therapy is often indicated in cases of long-lasting resistant pain. Apart from a traditional open resection, the modalities of minimally invasive surgery, such as radiofrequency ablation or cryoablation, have gradually become the option of choice in most cases. The first part of this manuscript is a minireview of the contemporary literature on the pathogenesis, diagnosis, and current trends in the treatment of osteoid osteoma. The second part is a case report of our own experience with a conventional C-arm-guided radiofrequency ablation of an osteoid osteoma located in the femoral neck in an adolescent patient. The aim was to prove that, even when more sophisticated guiding devices (CT, O-arm, etc.) are not available, the safe and reliable ablation of the lesion using a C-arm is still possible even in hard-to-reach areas. The case was a success, with no perioperative or postoperative complications.